Suppression of CX3CL1 by miR-497-5p inhibits cell growth and invasion through inactivating the ERK/AKT pathway in NSCLC cells. Issue 16 (18th August 2022) - Tang, Wen; Jia, Ping; Zuo, Lin; Zhao, Jia
ABSTRACT: Non-small cell lung cancer (NSCLC) is the most common lung cancer with a highest mortality rate. MiR-497-5p has been reported as tumor suppressor in many cancers, but the role and mechanism of miR-497-5p in regulating NSCLC progression are still largely unknown in vitro and in vivo. Here, miR-497-5p was significantly downregulated in human NSCLC tissues and cell lines, compared with matched adjacent tissues and normal lung epithelial cell line. Then, miR-497-5p mimic and inhibitor were, respectively, transfected into human NSCLC cells A549 and H460, CCK-8 assay, transwell assay, and flow cytometry were used to detect the capacities of cell proliferation, invasion and apoptosis. MiR-497-5p negatively regulated proliferation and invasion of NSCLC cancer cells. MiR-497-5p was demonstrated to directly bound to 3'-UTR of CX3CL1 mRNA and post-transcriptionally suppressed its expression thus inactivating its downstream oncogenic pathway ERK/AKT. Moreover, transfection with short hairpin RNA (shRNA) against CX3CL1 decreased capacity of cell proliferation and invasion and promoted cell apoptosis in NSCLC cells. In addition, ERK inhibitor U0126 attenuated the promotion effect of miR-497-5p inhibitor on activation of ERK/AKT and cell proliferation and migration. Finally, overexpression of miR-497-5p substantially suppressed activation of the ERK/AKT pathway and tumor growth in tumor-bearing mice in vivo. Taken together, our findings showed that miR-497-5p is downregulated in human NSCLC tissues and cell lines, and it inhibited tumor growth and cell invasion by targeting CX3CL1 gene to inactivate the ERK/AKT pathway in NSCLC cells.